DEVELOPMENT OF ACTIVE LEARNING AND PROJECT – BASE LEARNING INSTRUCTIONAL MODEL BASED ON BLENDED APPROACH TO ENHANCE COMPRETENCIES IN EDUCATIONAL INFORMATION TECHNOLOGY AND INNOVATION FOR PRE-SERVICE TEACHER OF RAJABHAT UNIVERSITY - Ounkaew, Direk; Meesuwan, Wiwat; Payakpate, Janjira (Journal of MCU Nakhondhat, 2023)
The purposes of this research were 1) to create and evaluate the quality of an active learning and project-based learning instructional model based on blended approach to enhance the competencies on educational innovation and information technology for pre-service teacher of Rajabhat University, 2) to try out the proposed instructional model, and 3) to evaluate the achievement of the proposed instructional model. The samples used for this research were 35 students of the third-year bachelor degree of education in childhood education major, faculty of Education, Nakhon Sawan Rajabhat University. Research findings were as follows: 1) an instructional model for enhancing the competencies on educational innovation and information technology for pre-service teacher of Rajabhat University consisted of four components: input, process, output and feedback. Five steps of process are researching, problem statement, brainstorming, observation, and synthesizing/ reflecting. These steps were inserted as the activities of the active learning and problem-based learning into both normal classroom (Face-to-Face Learning) and online classroom (Online Learning). Learners’ learning post-test achievements were higher than the pre-test achievements with statistical significance at .05. Overall mean score of the 1st competency, the ability to choose apply and evaluate media, innovation and Information Technology for learning, equaled 79.68%, a very good level. The 2nd competency was ability to use Information Technology for communication. Its overall mean score equaled 88.38%, a good level. Finally, The total mean score for learners’ opinion at the most level (Mean = 4.56, S.D. = 0.61). By the evaluation of five experts, this model was suitable for enhancing the competencies at the most level (Mean = 4.52, S.D.=0.51)